Hemozoin From the Liver Fluke, Opisthorchis felineus, Modulates Dendritic Cell Responses in Bronchial Asthma Patients - Saltykova, Irina V.; Ittiprasert, Wannaporn; Nevskaya, Kseniya V.; Dorofeeva, Yulia B.; Kirillova, Natalia A.; Kulikov, Evgeniy S.; Ivanov, Vladimir V.; Mann, Victoria H.; Pershina, Alexandra G.; Brindley, Paul J. (Frontiers in Veterinary Science, 2019)
Aims There is a general, inverse relationship between helminth infection and allergic diseases including bronchial asthma. Proteins and other mediators released from parasitic worms exert cogent down-modulation of atopic and other allergic reactivity. We investigated the immune activities of an immortalized murine dendritic cell line (JAWSII) and of primary human dendritic cells (hDC) collected from study participants with and without bronchial asthma (BS) after Opisthorchis felineus hemozoin (OfHz) treatment. Methods and Results In vitro, expression of lymphocyte activating factors, T helper 1 (Th1) induction and anti-inflammatory cytokines including tumor necrosis factor alpha (TNF-), interleukin-1beta (IL-1β), IL-10 and IL-12β increased significantly in murine dendritic cells (mDC) pulsed with OfHz. In parallel, primary dendritic cells (hDC) from cases clinically diagnosed with BA along with healthy controls were exposed ex vivo to OfHz in combination with LPS. Whereas, no significant change in the cellular maturation markers, CD83, CD86, CD40 was apparent in BA versus healthy hDC, pulsing hDC from BA with OfHz with LPS induced significant increases in expression of IL-10 and IL-12β, although not of TNF- or tumor growth factor-beta, TGF- β. Conclusions Liver fluke hemozoin OfHz stimulated production of Th1 inducer and anti-inflammatory cytokines IL-10 and IL-12β from BA-hDC pulsed with OfHz, and outcome that contributes to our understanding of the mechanisms whereby opisthorchiasis contributes to protection against the atopic disease in liver fluke infection-endemic regions.